Experiencing regularisation in Accra, Cape Town and Rio de Janeiro: The actual right to the city, neoliberalisation and everyday life. Issue 5 (2nd November 2018) - Morange, Marianne; Pilo', Francesca; Spire, Amandine
Abstract : In the prolific contemporary discussions on the right to the city, little attention has been paid to the multifaceted political meaning of the reshaping of city dwellers' rights, duties and responsibilities through regularisation processes inspired by neoliberal logics. This paper fills in this gap by engaging in an analysis of the dialectical relation between the political dimension of everyday life, urban rights, neoliberal urban policies and political emancipation. We thereby break from a radical reading of Lefebvre's notion and from a focus on political mobilisation in order to cast a new light on the debate on the right to the city. Three regularisation policies, all linked to the affirmation of a commercial or fiscal relationship to the state are considered through a cross-case analysis: the regularisation that followed the forced displacement of street traders in central Accra; an in situ process of regularisation of street trading in a Cape Town central market; the regularisation of electricity services in the favelas of Rio de Janeiro, a policy that seeks to re-establish a commercial relationship with favela residents by redefining their rights and responsibilities as registered customers of a private electricity provider. We resort to an exploratory notion, the actual right to the city, to examine how these forms of administrative regularisation have reshaped urban life. We argue that these processes of regularisation convey de-politicisation dynamics, such as the fragmentation and individualisation of political identities, along with the possible re-politicisation of certain stakes, such as the strengthening of individual and collective political expectations toward the State. This tension is due to the ambiguous nature of the new social and spatial contract between State and citizens emerging from regularisation. Beyond the necessary analysis of political struggles against neoliberal policies, and the essential assessment of their impact on urban inequalities, we therefore call for a better consideration of the ambiguous and less visible political impact of processes of selective inclusion and recognition by the State on the way city dwellers envision their rights and duties.